Steel part surface treatment method based on ultrasonic nanometer strengthening

By adopting ultrasonic nano-strengthening carbon-nitrogen boron co-permeation and ultrasonic surface nano-treatment methods on the steel parts, the problem of thermal fatigue in high temperature environments is solved, and the fatigue resistance of the steel parts is significantly improved.

CN119753565AActive Publication Date: 2025-04-04HUBEI MILALION METALLURGICAL MACHINERY CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411951749.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

Existing steels are prone to thermal fatigue cracks in high temperature environments, which affects their service life, and the existing technology is difficult to effectively solve this problem.

Method used

The surface treatment method of steel parts based on ultrasonic nanostrengthening is adopted, including carbon-nitrogen-boron co-permeation and ultrasonic surface nanotreatment. Modified nitrogen-doped carbon material is added to the carbonitridine co-permeable agent to improve the surface hardness and hardness gradient of steel parts through ultrasonic rolling technology.

Benefits of technology

The fatigue resistance of steel parts is significantly improved, and by forming a more uniform hardness gradient and denser nitride cementite, it effectively prevents the formation and expansion of fatigue cracks.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a steel part surface treatment method based on ultrasonic nanometer strengthening. The steel part surface treatment method comprises the following steps that a, a steel part is subjected to carbonitriding treatment; b, ultrasonic nanometer strengthening treatment is conducted on the steel part obtained in the step a and subjected to carbonitriding treatment; in the step a, a boronizing agent for carbonitriding treatment comprises a boronizing agent and a carbonitriding agent, and the carbonitriding agent comprises the following components in percentage by mass: 40-50% of carbon black and 30-40% of a modified nitrogen-doped carbon material; the preparation method of the modified nitrogen-doped carbon material comprises the following steps: adding sodium carboxymethyl cellulose into water, stirring to prepare sodium carboxymethyl cellulose hydrogel, adding NH4Cl to obtain NH4Cl / sodium carboxymethyl cellulose gel, drying, calcining, cooling to obtain a nitrogen-doped carbon material, adding the nitrogen-doped carbon material into a rare earth chloride aqueous solution, stirring, centrifuging, and drying to obtain the modified nitrogen-doped carbon material. The modified nitrogen-doped carbon material is obtained. According to the surface treatment method, the anti-fatigue performance of the steel part can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The patent of this invention relates to the technical field of metal surface treatment, and in particular to a method for surface treatment of steel parts based on ultrasonic nano-strengthening. Background Art

[0002] Steel is one of the most widely used structural materials in the world. It has a wide range of uses, covering almost all industrial and civil fields, including the construction industry, automobile industry, shipbuilding, machinery manufacturing, home appliance industry, infrastructure, aerospace, etc. Steel plays an important role in these fields due to its high strength, plasticity, toughness and cost-effectiveness. With the development of science and technology, the application areas of steel are constantly expanding. The performance of steel is directly related to the safety, reliability and economy of the product. With the development of industrial technology, the requirements for steel performance are also increasing. Although the existing steel production process is quite mature, the performance of existing steel is still insufficient in some specific application scenarios.

[0003] Many industrial applications of steel, such as hot working dies, heat exchangers, turbine blades, etc., work in high temperature environments. These components experience rapid changes in temperature during operation, resulting in thermal stress inside the material, thereby causing thermal fatigue cracks and affecting service life.

[0004] In view of this, it is necessary to study a method to improve the thermal fatigue performance of steel parts. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the prior art to a certain extent. Therefore, in a first aspect of the present invention, the present invention provides a method for surface treatment of steel parts based on ultrasonic nano-strengthening, comprising the following steps:

[0006] Step a: Carbo-nitrogen-boron co-diffusion treatment of the steel part;

[0007] Step b: performing ultrasonic surface nano-treatment on the steel part treated by carbonitriding and boronizing obtained in step a;

[0008] In the step a, the carbonitriding agent includes a boronizing agent and a carbonitriding agent, and the carbonitriding agent includes the following components by mass percentage: 40-50% carbon black, 30-40% modified nitrogen-doped carbon material, 6-10% sodium carbonate, 2-6% sodium chloride, and 6-10% sodium acetate;

[0009] The preparation method of the modified nitrogen-doped carbon material comprises the following steps:

[0010] Step 1): adding sodium carboxymethyl cellulose to water and stirring to obtain sodium carboxymethyl cellulose hydrogel, and then adding NH4Cl and dispersing to obtain NH4Cl / sodium carboxymethyl cellulose gel;

[0011] Step 2): drying, calcining, and cooling the NH4Cl / sodium carboxymethyl cellulose gel obtained in step 1) to obtain a nitrogen-doped carbon material;

[0012] Step 3): adding the nitrogen-doped carbon material to the rare earth chloride aqueous solution, stirring, centrifuging, and drying to obtain a modified nitrogen-doped carbon material;

[0013] In the step 1), the mass ratio of sodium carboxymethyl cellulose to NH4Cl is 5:8-12.

[0014] Through the above technical scheme, a modified nitrogen-doped carbon material is added to the carbonitriding agent. The addition of the modified nitrogen-doped carbon material is conducive to the co-infiltration of carbon and nitrogen to form iron-carbon-nitrogen compounds with iron. The modified nitrogen-doped carbon material uses sodium carboxymethyl cellulose and NH4Cl as carbon source and nitrogen source to effectively prevent dislocation movement, effectively improve the hardness of the carbonitriding layer, and more importantly, make the hardness of the surface layer, carbonitriding layer, and boriding layer closer, the hardness gradient is more moderate, and the deformation resistance is increased. In addition, more iron-nitrogen active sites in the steel are generated to generate more uniform and dense nitrogen-containing cementite, and the micro-deformation is homogenized, which effectively prevents the formation and expansion of fatigue cracks. The addition of rare earth modification to the nitrogen-doped carbon material is more conducive to carbon-nitrogen infiltration, so that there is no gap between the carbonitriding layer and the boriding layer. Furthermore, when the mass ratio of sodium carboxymethyl cellulose to NH4Cl is too low, the nitrogen-containing cementite structure has defects, resulting in reduced hardness, failure to form a uniform hardness gradient, and reduced thermal fatigue performance of the steel. When the mass ratio of sodium carboxymethyl cellulose to NH4Cl is too high, the diffusion rate is affected, the thickness of the carbonitriding layer becomes smaller, and the thermal fatigue performance of the steel is affected.

[0015] Preferably, in the carbonitriding agent, the mass ratio of the carbon black to the modified nitrogen-doped carbon material is 1-1.67:1.

[0016] Through the above technical scheme, on the one hand, the carbon-nitrogen ratio in the carbonitriding agent can be controlled to ensure the thickness of the carbonitriding layer; on the other hand, a carbonitriding layer with higher hardness and more uniform hardness gradient can be formed, thereby making the hardness gradient of the steel part more gentle and the thermal fatigue performance better.

[0017] Preferably, in step 2), the calcination temperature is 800-1000°C.

[0018] By controlling the calcination temperature through the above technical solution, the activity and diffusion rate of carbon can be improved, thereby improving the hardness and fatigue resistance of the steel.

[0019] Preferably, in step 3), the mass concentration of the rare earth chloride aqueous solution is 10-20%, and the mass volume ratio of the nitrogen-doped carbon material to the rare earth chloride aqueous solution is 1:30-50 mL.

[0020] Preferably, in step 3), the rare earth chloride aqueous solution is a lanthanum chloride aqueous solution or a cerium chloride aqueous solution.

[0021] Preferably, the weight ratio of the boronizing agent to the carbonitriding agent is 0.9-1.1:1.

[0022] Preferably, in step a, the co-infiltration temperature is 700-900° C., and the co-infiltration time is 3-5 h.

[0023] Preferably, the boronizing agent comprises the following components by mass percentage: 2-8% cerium chloride, 35-45% borax, 30-40% ferroboron alloy, 15-20% sodium fluorosilicate, and 1-5% ammonium chloride.

[0024] Preferably, the ultrasonic surface nano-treatment is ultrasonic surface rolling, the static pressure of the ultrasonic surface rolling is 200-400N, the ultrasonic frequency is 18-19kHz, the amplitude of the ultrasonic rolling processing head is 16-18μm, and the lateral feed rate is 0.2-0.8mm / min.

[0025] Ultrasonic surface rolling is an impact pressure finishing method, which is essentially a clever and reasonable improvement of the traditional surface calendering process by introducing high-power ultrasonic frequency mechanical vibration. The ultrasonic surface nano-processing tool head applies a certain amplitude of ultrasonic frequency mechanical vibration to the workpiece, and under a certain static pressure and feed speed, the work head transmits pressure and ultrasonic impact vibration to the surface of mechanical parts, using the cold shrinkage characteristics of metal at room temperature to make the material produce elastic and plastic deformation. This application combines ultrasonic surface rolling with carbon-nitrogen-boron co-diffusion treatment to improve the fatigue resistance of steel parts.

[0026] Preferably, the steel part is made of 15CrNiMo steel.

[0027] In a second aspect of the present invention, the present invention provides an application of the above-mentioned surface treatment method in improving the thermal fatigue performance of steel parts.

[0028] The beneficial effects of the present invention are:

[0029] 1. The present invention provides a surface treatment method for steel parts based on ultrasonic nano-strengthening, comprising performing carbonitriding and boronizing treatment on steel parts, wherein the penetrants for the carbonitriding and boronizing treatment include boronizing agents and carbonitriding agents, and the carbonitriding agents include carbon black and modified nitrogen-doped carbon materials. The modified nitrogen-doped carbon materials use sodium carboxymethyl cellulose and NH4Cl as carbon sources and nitrogen sources, so that the modified nitrogen-doped carbon materials have unique electrical conductivity and surface properties, can effectively prevent dislocation movement, and have more effective iron-nitrogen active sites in the steel, generate more uniform and dense nitrogen-containing cementite, and improve the hardness of the carbonitriding layer. More importantly, the hardness of the surface layer, the carbonitriding layer, and the boronizing layer is closer, the hardness gradient is more moderate, the micro-deformation is uniform, the deformation resistance is increased, and the formation and expansion of fatigue cracks are effectively prevented. In addition, when the mass ratio of sodium carboxymethyl cellulose to NH4Cl is too low, the nitrogen-containing cementite structure has defects, resulting in reduced hardness, failure to form a uniform hardness gradient, and reduced thermal fatigue performance of the steel. When the mass ratio of sodium carboxymethyl cellulose to NH4Cl is too high, the diffusion rate is affected, the thickness of the carbonitriding layer becomes smaller, and the thermal fatigue performance of the steel is affected. The surface treatment method of the present invention can significantly improve the fatigue resistance of steel parts.

[0030] 2. The present invention provides a method for surface treatment of steel parts based on ultrasonic nano-strengthening, which combines carbonitriding and boron co-penetration treatment with ultrasonic surface nano-treatment, has a simple process and greatly improves the fatigue resistance of steel parts. DETAILED DESCRIPTION

[0031] The present invention will be further described below in conjunction with specific examples, but the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. In the following examples, if specific conditions are not specified, they are carried out according to conventional conditions or conditions recommended by the manufacturer. The methods used are conventional methods known in the art unless otherwise specified, and the consumables and reagents used are commercially available unless otherwise specified. Unless otherwise specified, the professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the recorded content may also be applied to the present invention. Carbon black is carbon black N110 purchased from Longxing Chemical Co., Ltd. Water-soluble carbon black was purchased from the water-soluble pigment carbon black of Anyang Wangtai New Materials Co., Ltd.

[0032] Preparation Example 1

[0033] The preparation of modified nitrogen-doped carbon material comprises the following steps:

[0034] Step 1): 5 g of sodium carboxymethyl cellulose (CMC) was added to 180 mL of ultrapure water, and stirred to obtain sodium carboxymethyl cellulose hydrogel, and then 10 g of NH4Cl was added, and ultrasonicated for 30 min to obtain NH4Cl / sodium carboxymethyl cellulose gel;

[0035] Step 2): The NH4Cl / sodium carboxymethyl cellulose gel obtained in step 1) is dried and transferred to a tube furnace, nitrogen is introduced to exhaust the air in the tube, and then the tube furnace is heated to 900°C at a heating rate of 5°C / min, calcined and kept warm for 2h, and naturally cooled to room temperature to obtain a nitrogen-doped carbon material;

[0036] Step 3): prepare a 15% mass concentration of cerium chloride aqueous solution, take 200 mL of the cerium chloride aqueous solution, add 5 g of the nitrogen-doped carbon material prepared by the preparation method of step 2), stir at 80° C. for 2 h, centrifuge, and dry to obtain a modified nitrogen-doped carbon material.

[0037] Preparation Example 2

[0038] The difference between Preparation Example 2 and Preparation Example 1 is that the amount of NH4Cl used is different. In Preparation Example 2, the amount of NH4Cl used is 8 g.

[0039] Preparation Example 3

[0040] The difference between Preparation Example 3 and Preparation Example 1 is that the amount of NH4Cl used is different. In Preparation Example 3, the amount of NH4Cl used is 12 g.

[0041] Preparation Example 4

[0042] The difference between Preparation Example 4 and Preparation Example 1 is that in step 2), the calcination temperature is 800°C.

[0043] Preparation Example 5

[0044] The difference between Preparation Example 5 and Preparation Example 1 is that in step 2), the calcination temperature is 1000°C.

[0045] Preparation Example 6

[0046] The difference between Preparation Example 6 and Preparation Example 1 is that in step 3), cerium chloride is replaced by an equal mass of lanthanum chloride.

[0047] Preparation Example 7

[0048] The difference between Preparation Example 7 and Preparation Example 1 is that in step 1), NH4Cl is replaced by an equal mass of urea.

[0049] Preparation Example 8

[0050] The difference between Preparation Example 8 and Preparation Example 1 is that in step 1), sodium carboxymethyl cellulose (CMC) is replaced by an equal mass of water-soluble carbon black.

[0051] Preparation Example 9

[0052] The difference between Preparation Example 9 and Preparation Example 1 is that step 3) is not included, and the nitrogen-doped carbon material prepared in this Preparation Example is the nitrogen-doped carbon material prepared in step 2) of Preparation Example 1.

[0053] Preparation Example 10

[0054] The difference between Preparation Example 10 and Preparation Example 1 is that the amount of NH4Cl used is different. In Preparation Example 10, the amount of NH4Cl used is 6 g.

[0055] Preparation Example 11

[0056] The difference between Preparation Example 11 and Preparation Example 1 is that the amount of NH4Cl used is different. In Preparation Example 11, the amount of NH4Cl used is 15 g.

[0057] Example 1

[0058] Step a: 15CrNiMo steel is placed in a temperature-controlled furnace, a permeating agent is added, and carbon-nitrogen-boron co-permeating treatment is performed at a co-permeating temperature of 800°C for 4 hours. After heating is completed, the steel is cooled and taken out of the furnace.

[0059] The penetrant is composed of a boronizing agent and a carbonitriding agent in a weight ratio of 1:1.

[0060] Boriding agent (mass percentage): cerium chloride 5%, borax 40%, ferroboron alloy 36%, sodium fluorosilicate 17%, ammonium chloride 2%.

[0061] Carbonitriding agent (mass percentage): carbon black 45%, modified nitrogen-doped carbon material 35%, anhydrous sodium carbonate 8%, sodium chloride 4%, anhydrous sodium acetate 8%. The modified nitrogen-doped carbon material is the modified nitrogen-doped carbon material prepared by the preparation method of Preparation Example 1.

[0062] Step b: Use ultrasonic rolling equipment to perform ultrasonic rolling nano-strengthening treatment on the 15CrNiMo steel treated with carbonitriding and boron co-diffusion in step a. The static pressure of the ultrasonic rolling process is 300N, the spindle speed is 200rpm, the frequency of the ultrasonic generator is 18.5kHz, the amplitude of the ultrasonic rolling processing head is 17μm, the lateral feed rate is 0.5mm / min, and the number of treatments is 10 times.

[0063] Example 2

[0064] The difference between Example 2 and Example 1 is that the modified nitrogen-doped carbon material is a modified nitrogen-doped carbon material prepared by the preparation method of Preparation Example 2.

[0065] Example 3

[0066] The difference between Example 3 and Example 1 is that the modified nitrogen-doped carbon material is a modified nitrogen-doped carbon material prepared by the preparation method of Preparation Example 3.

[0067] Example 4

[0068] The difference between Example 4 and Example 1 is that the modified nitrogen-doped carbon material is a modified nitrogen-doped carbon material prepared by the preparation method of Preparation Example 4.

[0069] Example 5

[0070] The difference between Example 5 and Example 1 is that the modified nitrogen-doped carbon material is a modified nitrogen-doped carbon material prepared by the preparation method of Preparation Example 5.

[0071] Example 6

[0072] The difference between Example 6 and Example 1 is that in the carbonitriding agent, the mass percentages of carbon black and modified nitrogen-doped carbon material in the carbonitriding agent are different. In Example 6, the carbon black is 50% and the modified nitrogen-doped carbon material is 30%.

[0073] Example 7

[0074] The difference between Example 7 and Example 1 is that in the carbonitriding agent, the mass percentages of carbon black and modified nitrogen-doped carbon material in the carbonitriding agent are different. In Example 7, the carbon black is 40% and the modified nitrogen-doped carbon material is 40%.

[0075] Example 8

[0076] The difference between Example 8 and Example 1 is that the modified nitrogen-doped carbon material is the modified nitrogen-doped carbon material prepared by the preparation method of Preparation Example 6.

[0077] Comparative Example 1

[0078] The difference between Comparative Example 1 and Example 1 is that the modified nitrogen-doped carbon material is the modified nitrogen-doped carbon material prepared by the preparation method of Preparation Example 7.

[0079] Comparative Example 2

[0080] The difference between Comparative Example 2 and Example 1 is that the modified nitrogen-doped carbon material is the modified nitrogen-doped carbon material prepared by the preparation method of Preparation Example 8.

[0081] Comparative Example 3

[0082] The difference between Comparative Example 3 and Example 1 is that the modified nitrogen-doped carbon material is replaced by the nitrogen-doped carbon material prepared by the preparation method of Preparation Example 9.

[0083] Comparative Example 4

[0084] The difference between Comparative Example 4 and Example 1 is that the modified nitrogen-doped carbon material is replaced with an equal mass of carbon black.

[0085] Comparative Example 5

[0086] The difference between Comparative Example 5 and Example 1 is that the carbon black is replaced by an equal amount of modified nitrogen-doped carbon material.

[0087] Comparative Example 6

[0088] The difference between Comparative Example 6 and Example 1 is that the modified nitrogen-doped carbon material is the modified nitrogen-doped carbon material prepared by the preparation method of Preparation Example 10.

[0089] Comparative Example 7

[0090] The difference between Comparative Example 7 and Example 1 is that the modified nitrogen-doped carbon material is a modified nitrogen-doped carbon material prepared by the preparation method of Preparation Example 11.

[0091] The samples of Examples 1-8 and Comparative Examples 1-7 were subjected to thermal fatigue tests: the samples were subjected to a thermal fatigue tester at a temperature range of 20°C to 800°C, with the highest temperature maintained for 120s, and then cycled to perform thermal fatigue performance tests. The thermal fatigue performance was represented by the main crack length of the steel after the sample was subjected to 6000 thermal cycles. The results are shown in Table 1.

[0092] Table 1

[0093] Main crack length (μm) Example 1 53 Example 2 98 Example 3 89 Example 4 85 Example 5 76 Example 6 77 Example 7 93 Example 8 73 Comparative Example 1 128 Comparative Example 2 113 Comparative Example 3 243 Comparative Example 4 156 Comparative Example 5 268 Comparative Example 6 171 Comparative Example 7 196

[0094] Comparison between Example 1 and Example 1 shows that when the nitrogen source used in preparing the modified nitrogen-doped carbon material is changed, the thermal fatigue performance of the steel is reduced. Comparison between Example 2 and Example 1 shows that when the carbon source used in preparing the modified nitrogen-doped carbon material is changed, the thermal fatigue performance of the steel is reduced. This may be because when the carbon source is sodium carboxymethyl cellulose and the nitrogen source is NH4Cl, it is easier to avoid dislocation movement during carbonitriding, forming a higher hardness, more uniform hardness gradient, and thicker carbonitriding layer.

[0095] By comparing Comparative Example 3 with Example 1, it can be seen that when the nitrogen-doped carbon material is not modified with rare earth, the thermal fatigue performance of the steel deteriorates. This may be because, when no rare earth modification is added, the diffusion rate of carbonitriding is disordered, making the carbonitriding layer uneven, which in turn leads to poor thermal fatigue performance.

[0096] Comparison of Comparative Example 4 with Example 1 shows that when the modified nitrogen-doped carbon material is replaced with an equal mass of carbon black, the thermal fatigue performance of the steel deteriorates.

[0097] Comparison of Comparative Example 5 with Example 1 shows that when carbon black is replaced by modified nitrogen-doped carbon material of equal mass, the thermal fatigue performance of the steel deteriorates.

[0098] Comparison of Comparative Example 6 with Example 1 shows that when the mass ratio of sodium carboxymethyl cellulose to NH4Cl in the raw materials for preparing the modified nitrogen-doped carbon material is too high, the thermal fatigue performance of the steel is reduced.

[0099] Comparison of Comparative Example 7 with Example 1 shows that when the mass ratio of sodium carboxymethyl cellulose to NH4Cl in the raw materials for preparing the modified nitrogen-doped carbon material is too low, the thermal fatigue performance of the steel is reduced.

[0100] Comparison of Examples 2 and 3 with Example 1 shows that the mass ratio of sodium carboxymethyl cellulose and NH4Cl in the raw materials of the modified nitrogen-doped carbon material affects the thermal fatigue performance of the steel.

[0101] Comparison of Examples 4 and 5 with Example 1 shows that the calcination temperature during the preparation of the modified nitrogen-doped carbon material will affect the thermal fatigue performance of the steel.

[0102] Comparison of Examples 6 and 7 with Example 1 shows that the mass ratio of carbon black and modified nitrogen-doped carbon material in the carbonitriding agent affects the thermal fatigue properties of the steel.

[0103] By comparing Example 8 with Example 1, it can be seen that when the nitrogen-doped carbon material is modified with different rare earths, the thermal fatigue properties of the steel are different, and cerium chloride has a better effect. This may be because cerium chloride is more conducive to the penetration of the nitrogen-doped carbon material.

[0104] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are illustrative and are not to be construed as limitations on the present invention. A person skilled in the art may make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention, which shall all be included in the scope of protection of the present invention.

Claims

1. A method for surface treatment of steel parts based on ultrasonic nano-strengthening, characterized in that: The steps include: Step a: Carbo-nitrogen-boron co-diffusion treatment of the steel part; Step b: performing ultrasonic nano-strengthening treatment on the steel part treated by carbonitriding obtained in step a; In the step a, the carbonitriding agent includes a boronizing agent and a carbonitriding agent, and the carbonitriding agent includes the following components by mass percentage: 40-50% carbon black, 30-40% modified nitrogen-doped carbon material, 6-10% sodium carbonate, 2-6% sodium chloride, and 6-10% sodium acetate; The modified nitrogen-doped carbon material is prepared by the following preparation method: Step 1): adding sodium carboxymethyl cellulose to water and stirring to obtain sodium carboxymethyl cellulose hydrogel, and then adding NH4Cl and dispersing to obtain NH4Cl / sodium carboxymethyl cellulose gel; Step 2): drying, calcining, and cooling the NH4Cl / sodium carboxymethyl cellulose gel obtained in step 1) to obtain a nitrogen-doped carbon material; Step 3): adding the nitrogen-doped carbon material to the rare earth chloride aqueous solution, stirring, centrifuging, and drying to obtain a modified nitrogen-doped carbon material; In the step 1), the mass ratio of sodium carboxymethyl cellulose to NH4Cl is 5:8-12.

2. The method for surface treatment of steel parts based on ultrasonic nano-strengthening according to claim 1, characterized in that: In the carbonitriding agent, the mass ratio of the carbon black to the modified nitrogen-doped carbon material is 1-1.67:

1.

3. The method for surface treatment of steel parts based on ultrasonic nano-strengthening according to claim 1, characterized in that: In the step 2), the calcination temperature is 800-1000°C.

4. The method for surface treatment of steel parts based on ultrasonic nano-strengthening according to claim 1, characterized in that: In the step 3), the mass concentration of the rare earth chloride aqueous solution is 10-20%, and the mass volume ratio of the nitrogen-doped carbon material to the rare earth chloride aqueous solution is 1:30-50 mL.

5. The method for surface treatment of steel parts based on ultrasonic nano-strengthening according to claim 1, characterized in that: In the step 3), the rare earth chloride aqueous solution is a lanthanum chloride aqueous solution or a cerium chloride aqueous solution.

6. The method for surface treatment of steel parts based on ultrasonic nano-strengthening according to claim 1, characterized in that: The weight ratio of the boronizing agent to the carbonitriding agent is 0.9-1.1:

1.

7. The method for surface treatment of steel parts based on ultrasonic nano-strengthening according to claim 1, characterized in that: In the step a, the co-infiltration temperature is 700-900° C., and the co-infiltration time is 3-5 hours.

8. The method for surface treatment of steel parts based on ultrasonic nano-strengthening according to claim 1, characterized in that: The boronizing agent comprises the following components by mass percentage: 2-8% of cerium chloride, 35-45% of borax, 30-40% of ferroboron alloy, 15-20% of sodium fluorosilicate and 1-5% of ammonium chloride.

9. The method for surface treatment of steel parts based on ultrasonic nano-strengthening according to claim 1, characterized in that: The ultrasonic nano-strengthening treatment is ultrasonic surface rolling, the static pressure of the ultrasonic surface rolling is 200-400N, the ultrasonic frequency is 18-19kHz, the amplitude of the ultrasonic rolling processing head is 16-18μm, and the lateral feed rate is 0.2-0.8mm / min.

10. Use of the surface treatment method according to any one of claims 1 to 9 in improving the thermal fatigue performance of steel parts.

Citation Information

Patent Citations

  • Method for surface solid co-permeation on blade of cutter

    CN110158023A

  • Boron carbon nitrogen trielement coexudation method

    CN1442504A

  • Method for fabricating catalytic 3D network material

    US20160329572A1